Interspecific competition between two partridges in farmland landscapes. (July 2020) - Rinaud, Tony; Harmange, Clément; Pays, Olivier; Sarasa, Mathieu; Saillard, Maxime; Bretagnolle, Vincent
Abstract : Interspecific competition is expected to occur between phylogenetically closely related species when sharing resources. In birds, interspecific competition often occurs by song-mediated interference and frequently implies asymmetrical outcomes between the species pairs involved. Habitat loss resulting from agricultural intensification is expected to have aggregated bird species in the remaining suitable habitats, thus increasing the likelihood of interspecific competition. However, this process has rarely been considered as a potential factor limiting population recovery in farmland birds. We investigated whether interspecific competition occurs between grey, Perdix perdix, and red-legged, Alectoris rufa, partridges, two phylogenetically related species. Originally parapatric, they have suffered an artificial increase in their contact zone due to huge human-mediated gamebird releases. We analysed territorial behaviour through a playback stimuli experiment and investigated shifts in habitat niche in the absence and presence of a hypothetical competitor. Results showed that the grey partridge appeared less territorial when co-occurring with the red-legged partridge and shifted its habitat niche away from the latter, while no such change was detected for the red-legged partridge. These asymmetrical patterns in behaviour and ecology are predicted under an interspecific competition scenario beneficial to the red-legged partridge, and therefore suggest that they are competitively dominant to grey partridges where they co-occur. This result has potentially strong implications for the management of grey partridges as gamebirds, and for their conservation in areas where they are almost extirpated.